Hierarchical hybrids of carbon nanotubes in amphiphilic poly(ethylene oxide)-block-polyaniline through a facile method from smooth to thorny - Yang, Zhifang (Langmuir : the ACS journal of surfaces and colloids, 2013)
A facile approach was developed to synthesize conjugated block copolymer (BCP) poly(ethylene oxide)-b-polyaniline (PEO-PANI). Aldehyde group-terminated PEO was prepared by an esterification reaction of p-formylbenzoic acid and PEO and then reacted with PANI from chemical oxidative polymerization. FT-IR, (1)H NMR, and GPC results indicated that BCPs with different PEO block lengths were successfully synthesized. Moreover, the BCPs were employed to noncovalently modify multiwalled carbon nanotubes (MWNTs) through either the direct or indirect method. In the former method, transmission electron microscopy images showed that a core-shell MWNTBCP hybrid with a shell thickness of gyration diameter of PEO block (2Rg,PEO) was obtained in 1-methyl-2-pyrrolidone (NMP). These hybrids can be well dispersed in many common solvents and poly(vinyl alcohol) matrix. With the increase of PEO block length, the stability of the MWNT dispersion would be highly improved. Interestingly, in the indirect method where deionized water was added to the NMP solution of BCP/MWNT mixture, the surface of the hybrid micelles encapsulated with MWNTs changed from smooth into hierarchically thorny with the increase of BCP/MWNT weight ratio. In this case, the water contact angle had a minimum value of ~70° at the ratio of 1/8, indicating that the hierarchical thorns followed a Cassie-Baxter regime rather than a Wenzel one. A possible formation mechanism of the unique structure was also proposed